2018
DOI: 10.1080/01650424.2017.1420803
|View full text |Cite
|
Sign up to set email alerts
|

Sympatric occurrence of three leaf beetle species ofMacropleaSamouelle, 1819 (Coleoptera, Chrysomelidae, Donaciinae) in Finland with a key to species in Northern Europe

Abstract: Macroplea Samouelle, 1819 is the only known fully aquatic leaf beetle genus with three European species that have earlier been classified by their assumed water salinity preferences. We studied the inter-and intraspecific variation of the specimens living in Northern Europe using both molecular (cytochrome c oxidase subunit I, COI) and morphological evidence. The variation in the COI sequences between M. mutica (Fabricius, 1792) and M. pubipennis (Reuter, 1875) was 8.4-9%, M. mutica and M. appendiculata (Panze… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(5 citation statements)
references
References 23 publications
1
4
0
Order By: Relevance
“…The morphological character states recorded in this study are similar to those shown in Lou et al (2011), but there are some differences: elytral spines longer; black spots on pronotum larger. The median lobe and tegmen morphology are consistent with that shown by Lou et al (2011) andVahtera et al (2018). The endophallus is only shown in Lou et al (2011) and there were some differences, particularly in the shape of PDS.…”
Section: Discussionsupporting
confidence: 80%
See 4 more Smart Citations
“…The morphological character states recorded in this study are similar to those shown in Lou et al (2011), but there are some differences: elytral spines longer; black spots on pronotum larger. The median lobe and tegmen morphology are consistent with that shown by Lou et al (2011) andVahtera et al (2018). The endophallus is only shown in Lou et al (2011) and there were some differences, particularly in the shape of PDS.…”
Section: Discussionsupporting
confidence: 80%
“…In this study, the examination of M. mutica in Aomori Prefecture showed that the length of metatarsomere II equals metatarsomere I. Vahtera et al . (2018) also reported this character state, but Hayashi and Shiyake (2001), Warchałowski (2010) and Hayashi (2020) showed that the length of metatarsomere II is longer than that of metatarsomere I. Hayashi (2012) and Lou et al . (2011) reported that the length of metatarsomere II equals or is slightly longer than that of metatarsomere I.…”
Section: Resultsmentioning
confidence: 97%
See 3 more Smart Citations